2022
DOI: 10.1186/s12961-022-00931-1
|View full text |Cite
|
Sign up to set email alerts
|

Status of the health information system in Ireland and its fitness to support health system performance assessment: a multimethod assessment based on stakeholder involvement

Abstract: Background Between 2019 and 2021, the first Irish health system performance assessment (HSPA) framework was developed. As routinely collected health data are necessary to continuously populate indicators of an HSPA framework, a purpose-driven assessment of the health information system (HIS) in Ireland and its fitness to support the implementation of an HSPA framework was conducted. This study reports on the status of the Irish HIS through a multimethod assessment based on continuous broad stak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Algunos servicios de atención médica involucran la generación de datos de imágenes en tiempo real de alta resolución, que pueden variar desde alta definición (HD) hasta 4K, dependiendo de la situación clínica. Esto plantea dificultades significativas en la gestión de la tecnología por parte de los hospitales, ya que no cuentan con la capacidad para almacenar archivos de ese tamaño (Ivanković et al, 2023).…”
Section: Barreras Y Desafíos Para La Implementación De Una Gobernanza...unclassified
“…Algunos servicios de atención médica involucran la generación de datos de imágenes en tiempo real de alta resolución, que pueden variar desde alta definición (HD) hasta 4K, dependiendo de la situación clínica. Esto plantea dificultades significativas en la gestión de la tecnología por parte de los hospitales, ya que no cuentan con la capacidad para almacenar archivos de ese tamaño (Ivanković et al, 2023).…”
Section: Barreras Y Desafíos Para La Implementación De Una Gobernanza...unclassified
“…Recent years have seen a rapid digitalisation of care in Irish hospital settings, with a particular focus on the introduction of an Electronic Patient Record (EPR) (Ivanković, Jansen, Barbazza, Fernandes, Klazinga, & Kringos, 2022). While the advantages of EPR over traditional paper health records are well-described in the literature, recent studies have shown that usability of health IT systems remains suboptimal (Carayon & Hoonakker, 2019;Menachemi & Collum, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Decree of the Government of the Voronezh Region No. 116 dated 05.03.2022 "On Approval of the List of Settlements of the Voronezh Region Subject to the Threat of Forest and Other Landscape (Natural) Fires in 2022 and the List of Territories of Organizations for Recreation and Recreation of Children, Territories of Gardening or Horticulture of the Voronezh Region, exposed to the threat of forest fires in 2022" on the territory of the Voronezh region included 847 settlements, 35 children's recreation and recreation organizations, 93 gardening or horticulture, which are subject to the threat of forest and other landscape (natural) fires [3].…”
Section: Introductionmentioning
confidence: 99%